Anatomical Study of Hemorrhoidal Diseases - Hamid, Asadullah (Journal of Natural Sciences – Kabul University, 2020)
Hemorrhoids are a rectal disease caused by venous inflammation. The rectal canal consists of bones, muscles, collagen and elastic fibers, and blood vessels. Hemorrhoids generally appear in two forms: internal and external. Various factors contribute to the development of hemorrhoids, such as age, obesity, pregnancy in women, a lack of fiber in the diet, inadequate fluid intake, prolonged sitting on the toilet, anal sex, and rupture of the anal veins. Physical examination is crucial for diagnosing hemorrhoids. Treatment options for hemorrhoids are often divided into non-operative management, office procedures, and surgical management requiring an operating room. In conclusion, hemorrhoids are a common, complex, and multifaceted condition. There are various non-operative and operative treatments, each with its benefits. Treatment should be individualized based on the type and severity of symptoms, as well as considering the patient's other medical conditions.